Hybridization and gene expression: Beyond differentially expressed genes - Anna Runemark; Emily C. Moore; Erica L. Larson (Molecular Ecology, 2025)
Gene expression has a key role in reproductive isolation, and studies of hybrid gene expression have identified mechanisms causing hybrid sterility. Here, we review the evidence for altered gene expression following hybridization and outline the mechanisms shown to contribute to altered gene expression in hybrids. Transgressive gene expression, transcending that of both parental species, is pervasive in early generation sterile hybrids, but also frequently observed in viable, fertile hybrids. We highlight studies showing that hybridization can result in transgressive gene expression, also in established hybrid lineages or species. Such extreme patterns of gene expression in stabilized hybrid taxa suggest that altered hybrid gene expression may result in hybridization‐derived evolutionary novelty. We also conclude that while patterns of misexpression in hybrids are well documented, the understanding of the mechanisms causing misexpression is lagging. We argue that jointly assessing differences in cell composition and cell‐specific changes in gene expression in hybrids, in addition to assessing changes in chromatin and methylation, will significantly advance our understanding of the basis of altered gene expression. Moreover, uncovering to what extent evolution of gene expression results in altered expression for individual genes, or entire networks of genes, will advance our understanding of how selection moulds gene expression. Finally, we argue that jointly studying the dual roles of altered hybrid gene expression, serving both as a mechanism for reproductive isolation and as a substrate for hybrid ecological adaptation, will lead to significant advances in our understanding of the evolution of gene expression.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Biodiversity of octopuses in the Americas - Roberto González-Gómez; Otilio Avendaño; Irene de los Angeles Barriga-Sosa; Penélope Bastos; Claudia Caamal-Monsreal; Gabriela Castillo-Estrada; Celso Cedillo-Robles; Adam Daw; Mariana Díaz-Santana-Iturrios; Gabriela Galindo-Cortes; Jürgen Guerrero-Kommritz; Manuel Haimovici; et al. (Marine Biology, 2024)

Pollen effects in a changing climate: Ragweed pollen exposure and sleepiness in immunotherapy patients of a Southeastern Michigan allergy clinic - Peter S. Larson; Allison L. Steiner; Erica Bennion; Alan P. Baptist; Marie S. O’Neill; Carina J. Gronlund (International Journal of Biometeorology, 2024)

Global patterns of allochthony in stream–riparian meta‐ecosystems - Daniel C. Allen; James Larson; Christina A. Murphy; Erica A. Garcia; Kurt E. Anderson; Michelle H. Busch; Alba Argerich; Alice M. Belskis; Kierstyn T. Higgins; Brooke E. Penaluna; Veronica Saenz; Jay Jones; et al. (Ecology Letters, 2024)
Ecosystems that are coupled by reciprocal flows of energy and nutrient subsidies can be viewed as a single “meta‐ecosystem.” Despite these connections, the reciprocal flow of subsidies is greatly asymmetrical and seasonally pulsed. Here, we synthesize existing literature on stream–riparian meta‐ecosystems to quantify global patterns of the amount of subsidy consumption by organisms, known as “allochthony.” These resource flows are important since they can comprise a large portion of consumer diets, but can be disrupted by human modification of streams and riparian zones. Despite asymmetrical subsidy flows, we found stream and riparian consumer allochthony to be equivalent. Although both fish and stream invertebrates rely on seasonally pulsed allochthonous resources, we find allochthony varies seasonally only for fish, being nearly three times greater during the summer and fall than during the winter and spring. We also find that consumer allochthony varies with feeding traits for aquatic invertebrates, fish, and terrestrial arthropods, but not for terrestrial vertebrates. Finally, we find that allochthony varies by climate for aquatic invertebrates, being nearly twice as great in arid climates than in tropical climates, but not for fish. These findings are critical to understanding the consequences of global change, as ecosystem connections are being increasingly disrupted.

Whole exome sequencing of wild-derived inbred strains of mice improves power to link phenotype and genotype - Peter L. Chang; Emily Kopania; Sara Keeble; Brice A. J. Sarver; Erica Larson; Annie Orth; Khalid Belkhir; Pierre Boursot; François Bonhomme; Jeffrey M. Good; Matthew D. Dean (Mammalian Genome, 2017)

Heterogeneous genome divergence, differential introgression, and the origin and structure of hybrid zones - Richard G. Harrison; Erica L. Larson (Molecular Ecology, 2016)
Hybrid zones have been promoted as windows on the evolutionary process and as laboratories for studying divergence and speciation. Patterns of divergence between hybridizing species can now be characterized on a genomewide scale, and recent genome scans have focused on the presence of ‘islands’ of divergence. Patterns of heterogeneous genomic divergence may reflect differential introgression following secondary contact and provide insights into which genome regions contribute to local adaptation, hybrid unfitness and positive assortative mating. However, heterogeneous genome divergence can also arise in the absence of any gene flow, as a result of variation in selection and recombination across the genome. We suggest that to understand hybrid zone origins and dynamics, it is essential to distinguish between genome regions that are divergent between pure parental populations and regions that show restricted introgression where these populations interact in hybrid zones. The latter, more so than the former, reveal the likely genetic architecture of reproductive isolation. Mosaic hybrid zones, because of their complex structure and multiple contacts, are particularly good subjects for distinguishing primary intergradation from secondary contact. Comparisons among independent hybrid zones or transects that involve the ‘same’ species pair can also help to distinguish between divergence with gene flow and secondary contact. However, data from replicate hybrid zones or replicate transects do not reveal consistent patterns; in a few cases, patterns of introgression are similar across independent transects, but for many taxa, there is distinct lack of concordance, presumably due to variation in environmental context and/or variation in the genetics of the interacting populations.

Distribution and dietary regulation of an associated facultative Rhizobiales-related bacterium in the omnivorous giant tropical ant, Paraponera clavata - Hannah K. Larson; Shana K. Goffredi; Erica L. Parra; Orlando Vargas; Adrián A. Pinto-Tomas; Terrence P. McGlynn (The Science of Nature, 2014)

Reproductive Success and Body Size in the Cricket Gryllus firmus - Nicholas W. Saleh; Erica L. Larson; Richard G. Harrison (Journal of Insect Behavior, 2014)

Gene flow and the maintenance of species boundaries - Erica L. Larson; Thomas A. White; Charles L. Ross; Richard G. Harrison (Molecular Ecology, 2014)
Hybrid zones are regions where individuals from genetically differentiated populations meet and mate, resulting in at least some offspring of mixed ancestry. Patterns of gene flow (introgression) in hybrid zones vary across the genome, allowing assessment of the role of individual genes or genome regions in reproductive isolation. Here, we document patterns of introgression between two recently diverged species of field crickets. We sampled at a very fine spatial scale and genotyped crickets for 110 highly differentiated single nucleotide polymorphisms ( SNP s) identified through transcriptome scans. Using both genomic and geographic cline analysis, we document remarkably abrupt transitions (

Cryptic gametic interactions confer both conspecific and heterospecific advantages in the Chrysochus (Coleoptera: Chrysomelidae) hybrid zone - Merrill A. Peterson; Erica L. Larson; Margaret Brassil; Kati J. Buckingham; Danielle Juárez; Joseph Deas; Donna Mangloña; Michael A. White; Jonathan Maslan; Andrew Schweitzer; Kirsten J. Monsen (Genetica, 2011)